Emission analysis of diesel and butanol blends in research diesel engine - Joy, Nivin; Balan, K. N.; Nagappan, Beemkumar; Justin Abraham baby, Sajin (Petroleum science and technology, 2020)
This study is aimed at reducing NOx, Smoke, HC, CO emissions from single-cylinder, four-stroke, and water cooled diesel engine. The research engine is fueled with diesel and two blends of butanol and diesel at atmospheric conditions. Neat diesel is termed as D100, 10%, and 20% Volume of butanol dispersed in D100 is termed as D90B10 and D80B20 respectively. The chemical and physical properties of D100, D90B10 and D80B20 fall within the limits of ASTM standards. Results revealed that enhanced chemical properties and higher latent heat of vaporization of butanol lowered the CO, HC, smoke, and NO X emissions of diesel fueled research diesel engine.